Method for improving the bond strength of fiber reinforced polypropylene composites to aluminum alloys
Patent Information
- Application Number
- CN202611163294.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-08-03
AI Technical Summary
[0004]针对现有技术的不足,本发明提供了提高纤维增强聚丙烯复合材料与铝合金结合强度的方法,解决了异质材料在热压复合成型过程中,由于金属与聚合物基体之间的理化性质差异,界面处难以形成稳定的连接结构,且常规加工易导致界面处聚合物熔体填充不充分
1、本发明通过在金属基板表面采用多条微线段重复扫描的方式加工微观网格沟槽,分散了激光加工时的局部热量,减少了沟槽边缘再铸金属的堆积,从而保持沟槽开口通畅;复合熔体进入沟槽并受槽壁限制结晶固化后形成机械嵌固节点,该结构能直接传递载荷并阻碍界面滑移,有效提高了复合材料与铝合金的界面结合强度。
Smart Images

Figure CN122645509B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite material processing and molding technology, specifically to a method for improving the bonding strength between fiber-reinforced polypropylene composite materials and aluminum alloys. Background Technology
[0002] With the development of lightweighting in manufacturing fields such as aerospace, new energy vehicles, and consumer electronics, metal-plastic composites that combine the mechanical properties of metals with the lightweight and easy-to-process characteristics of plastics have attracted attention. Among them, the composite of aluminum alloy and glass fiber reinforced polypropylene shows potential in balancing cost and performance. However, the low surface energy of aluminum alloy and the high crystallinity of polypropylene, along with the differences in their physicochemical properties, lead to poor interfacial compatibility.
[0003] Currently, the main methods for achieving metal-plastic composites include mechanical bonding, adhesive bonding, and direct thermoplastic bonding. Mechanical bonding introduces voids in the material, leading to stress concentration, weakening the matrix strength, and increasing structural weight, making it difficult to meet integrated lightweight design requirements. Adhesive bonding suffers from long processing cycles, stringent curing environment requirements, and unstable aging and damp heat resistance, and is prone to releasing volatile organic compounds. Thermoplastic bonding methods such as laser welding and ultrasonic welding have poor adaptability to material optical properties, component dimensions, and geometries. When performing large-area planar composites and processing high-glass fiber reinforced materials, they are prone to defects such as uneven energy transfer, fiber distribution disruption, inadequate welding, or overheating, making it difficult to guarantee uniform and high-strength interfacial bonding. Therefore, achieving a high-strength and stable interfacial bond between aluminum alloys and fiber-reinforced polypropylene is a technical problem that needs to be solved in the application of this composite material. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention provides a method for improving the bonding strength between fiber-reinforced polypropylene composites and aluminum alloys. This method solves the problem that during the hot-pressing composite molding process of heterogeneous materials, the difference in physicochemical properties between the metal and polymer matrix makes it difficult to form a stable bonding structure at the interface, and conventional processing often results in insufficient polymer melt filling at the interface. Furthermore, during the cooling and solidification stage, residual thermal stress is easily generated due to differences in material shrinkage rates, leading to low interfacial bonding strength between the final fiber-reinforced polypropylene composite and the aluminum alloy.
[0005] To achieve the above objectives, the present invention provides the following technical solution: a method for improving the bonding strength between fiber-reinforced polypropylene composite materials and aluminum alloys, comprising: Aluminum alloy sheet is processed into metal substrate, and polypropylene matrix is melt-blended with glass fiber and granulated to obtain composite granules; A laser beam is output along a grid-like scanning path on the surface of the metal substrate to process micro-grid trenches. A mold with a mold cavity is provided, the metal substrate is positioned in the mold cavity, the composite granules are laid on the area of the metal substrate with the micro-grid grooves, the mold is closed, the mold is heated to transform the composite granules into a composite melt, and molding pressure is applied and held to allow the composite melt to enter the interior of the micro-grid grooves. The mold, which is in a closed state, is cooled to allow the composite melt located inside the micro-grid grooves to crystallize and solidify, resulting in a composite component. The mold is then opened to remove the composite component.
[0006] Micro-grid grooves are fabricated on the surface of aluminum alloy to provide physical anchoring space for the composite melt. Heating and pressurizing within a mold allows the molten polypropylene and glass fiber system to infiltrate and fill the grooves. After cooling and solidification, the polypropylene material and the metal grooves form a mechanically interlocking structure at the microscopic level, increasing the interfacial contact area and mechanical interlocking force between them, thereby improving the overall bonding strength of the composite component.
[0007] In a preferred embodiment of the present invention, when a laser beam is output on the surface of the metal substrate according to a grid-shaped scanning path, the grid-shaped scanning path includes multiple grid lines, and each grid line is composed of multiple parallel micro-segments arranged side by side, and the complete grid pattern formed by the multiple grid lines is scanned repeatedly in multiple passes. The plurality of parallel micro-segments are three in number, and the physical spacing between adjacent micro-segments is 10 μm; The center-to-center spacing between adjacent grid lines is set to 0.07 mm to 0.7 mm.
[0008] Multiple micro-segments are processed side-by-side to create a single grid line, increasing the actual physical width of each micro-groove. By setting the center-to-center spacing between grid lines, the distribution density of micro-grooves on the metal substrate surface per unit area is controlled, ensuring a sufficient number of anchoring nodes are formed on the aluminum alloy surface while preventing a decrease in the strength of the metal substrate due to overly dense groove layout.
[0009] In a preferred embodiment of the present invention, when a laser beam is output on the surface of the metal substrate, a single micro-line segment is scanned twice along the same path before the complete mesh pattern is processed once, which is defined as one processing pass. The process of repeatedly scanning the complete mesh pattern formed by the multiple mesh lines specifically involves performing a total of 10 scans on the complete mesh pattern to achieve a depth-to-width ratio of 0.5 for the processed micro-mesh grooves.
[0010] By specifying the number of repeated scans along the same path and the cumulative number of scan passes, the removal rate of metal material during laser processing is controlled, resulting in a specific aspect ratio of 0.5 for the formed micro-grid grooves. This aspect ratio range matches the flow viscosity characteristics of the polypropylene composite melt, allowing the pressurized melt to smoothly expel air from the inside of the groove and reach the bottom of the groove, forming a dense, solidified node without pores.
[0011] In a preferred embodiment of the present invention, after the aluminum alloy sheet is processed into a metal substrate, the metal substrate is subjected to surface cleaning and dehumidification treatment. After the micro-grid trenches are fabricated and before the composite granules are laid, the surface of the metal substrate is cleaned, including: The metal substrate with the micro-grid grooves is subjected to surface polishing to remove the protruding recast metal nodules on the surface of the metal substrate. The polished metal substrate is placed in an ultrasonic cleaner for cleaning to remove tiny particles remaining inside and at the edges of the micro-grid grooves. The cleaned metal substrate is dried with hot air to expose the openings and internal spaces of the micro-grid trenches.
[0012] A grinding and ultrasonic cleaning process is incorporated after the laser processing step to remove recast metal nodules and loosely attached particles generated by high-energy laser ablation, preventing these residual impurities from forming a weak layer at the bonding interface. A hot air drying process removes any residual cleaning liquid, ensuring no interface obstruction when the subsequent melt wets the metal surface.
[0013] In a preferred embodiment of the present invention, when the metal substrate is positioned in the mold cavity, metal gaskets are placed in the non-connection areas at both ends of the metal substrate, and the metal gaskets serve as limiting members. The thickness of the metal pad is consistent with the thickness of the metal substrate, so as to stabilize the pressure distribution applied to the region of the metal substrate with the micro-grid grooves when the mold is closed.
[0014] During mold closing, a shim of the same thickness as the metal substrate is used to perform physical height limiting, maintaining the height uniformity of the mold cavity in the closed state. This operation ensures that the molding pressure applied to the composite granule laying area is evenly distributed, avoiding uneven local pressure distribution that could lead to insufficient melt filling or bending deformation of the metal substrate.
[0015] In a preferred embodiment of the present invention, the target temperature for heating the mold is configured to be between 190°C and 230°C.
[0016] The target heating temperature range corresponds to the suitable melting state of the polypropylene matrix, so that the material exhibits a low melt viscosity to facilitate penetration into the micro-grid grooves and prevent the polypropylene polymer chain segments from undergoing thermal degradation due to excessive heating temperature.
[0017] In a preferred embodiment of the present invention, the mass fraction of glass fiber in the composite granules is configured to be 20%, and the target temperature for heating the mold is 210°C to 230°C.
[0018] For composite material systems with a specific mass fraction of glass fiber, the lower limit of the target heating temperature is increased to compensate for the increase in overall melt flow resistance caused by the addition of glass fiber, and to maintain the wetting and filling ability of the fiber-containing melt system for the microscopic surface morphology of metal.
[0019] In a preferred embodiment of the present invention, the process of melt blending and granulating the polypropylene matrix with the glass fiber includes: feeding the polypropylene matrix and the glass fiber into a twin-screw extruder for melt blending and extrusion molding; The rotational speed and screw combination of the twin-screw extruder are checked according to the critical length of the glass fiber to avoid excessive breakage of the glass fiber; The critical length is estimated based on the shear hysteresis theory and determined by the following relationship: the product of the tensile breaking strength of the glass fiber and the cross-sectional diameter of the glass fiber, divided by twice the interfacial shear strength between the glass fiber and the polypropylene matrix.
[0020] Based on the shear hysteresis theory, the critical length for load transfer of glass fibers is calculated, and the speed and screw combination parameters of the extrusion equipment are adjusted according to the calculation results. This control method limits the mechanical shear strength during the blending process, preventing the glass fibers from breaking below the critical size due to excessive stress during the granulation stage, thus preserving the load-bearing and mechanical reinforcement functions of the fibers in the final composite component.
[0021] In a preferred embodiment of the present invention, when cooling the mold in a closed state, the mold is kept closed during the cooling stage to limit the thickness direction deformation of the composite melt located inside the micro-grid grooves during the crystallization and solidification process; The micro-grid grooves form a geometric constraint on the crystallized and solidified composite melt, constituting a mechanically embedded node. The mechanically embedded node is used to resist the debonding or slippage of the composite component along the interface direction under tensile load.
[0022] During the cooling and shrinkage phase, the rigidity of the mold cavity is maintained to control the dimensional deformation of the composite material in the thickness direction. The cured composite material combines with the sidewalls of the micro-grid grooves to form mechanically embedded nodes. Under load, the peeling shear force in the interface direction is converted into a normal blocking force of the groove sidewalls on the embedded material, thus hindering the debonding and failure process of the interface.
[0023] In a preferred embodiment of the present invention, after opening the mold and removing the composite component, the composite component is placed in a static storage state, the static storage state comprising: The removed composite component was placed horizontally in a dry environment at room temperature and left to stand for 48 hours. During static storage, the area in the composite component where the metal substrate is joined to the crystallized and solidified composite melt is not subjected to external clamping force and bending load, so as to release the shrinkage thermal stress remaining during cooling due to the difference in the coefficient of thermal expansion between the metal substrate and the crystallized and solidified composite melt.
[0024] After demolding, a room-temperature static storage process without external load constraints is set up to provide a time window for stress relaxation in heterogeneous components composed of metal and polymer composite materials. This process causes the spontaneous release of residual interfacial shrinkage thermal stress accumulated during the cooling stage due to the difference in thermal expansion coefficients between the aluminum alloy and the composite material, thereby reducing the internal stress level and maintaining the stability of the initial interfacial bonding strength of the component.
[0025] This invention provides a method for improving the bonding strength between fiber-reinforced polypropylene composites and aluminum alloys. It has the following beneficial effects: 1. This invention processes micro-grid trenches on the surface of a metal substrate by repeatedly scanning multiple micro-segments, which disperses the local heat during laser processing and reduces the accumulation of recast metal at the trench edges, thereby keeping the trench opening unobstructed. After the composite melt enters the trench and is restricted by the trench wall to crystallize and solidify, it forms a mechanically embedded node. This structure can directly transfer loads and hinder interface slippage, effectively improving the interfacial bonding strength between the composite material and the aluminum alloy.
[0026] 2. This invention adjusts the rheological properties of polypropylene in the molten state by matching the heating temperature of hot pressing with the glass fiber content of the composite granules, so that the composite material has a suitable viscosity and fills the micro-grid grooves under molding pressure. This method avoids poor filling of the groove bottom caused by excessive viscosity, and also prevents melt overflow and insufficient system pressure caused by excessively low viscosity, thus ensuring the interface contact area and composite molding quality.
[0027] 3. This invention restricts the free shrinkage of the composite material in the thickness direction by keeping the mold closed during the cooling stage, and places the composite component in a room temperature environment for unloaded static storage after demolding. This process releases the interfacial shrinkage thermal stress caused by the difference in thermal expansion coefficients between the aluminum alloy and the composite material, prevents residual stress from weakening the mechanical connection between the dissimilar materials, and maintains the structural stability of the composite component. Attached Figure Description
[0028] Figure 1 A flowchart illustrating the overall process of the method for improving the bonding strength between fiber-reinforced polypropylene composite materials and aluminum alloys provided by the present invention. Figure 2 This is a flowchart illustrating the preparation of the metal substrate and composite granules in this invention; Figure 3 This is a flowchart illustrating the process of forming micro-grid trenches on the surface of a metal substrate in this invention. Figure 4 This is a flowchart illustrating the physical bonding of a metal substrate and composite granules via hot pressing in this invention. Figure 5 This is a flowchart illustrating the process of controlling the cooling and curing of the composite material in this invention; Figure 6 This is a laser scanning route diagram in the present invention; Figure 7 This is a diagram of the aluminum-plastic composite structure in this invention; Figure 8 This is a schematic diagram of the gasket structure in this invention. Detailed Implementation
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] See attached document Figure 1 This invention provides a method for improving the bonding strength between fiber-reinforced polypropylene composite materials and aluminum alloys, comprising the following steps: S10, Preparation of metal substrates and composite granules. Cutting equipment processes aluminum alloy sheets into metal substrates of a set size, and cleaning equipment removes oil, processing residue, and surface impurities from the metal substrate surface; The extrusion granulation equipment melt-blends and granulates the polypropylene matrix with glass fiber to obtain composite granules; the drying equipment dehumidifies the cleaned metal substrate and the prepared composite granules to reduce the probability of forming interface bubbles or pores during the subsequent hot pressing process.
[0031] S20, a micro-grid trench is formed on the surface of the metal substrate. After the surface is dried, the metal substrate is transferred to a laser processing device, and the laser emitting device outputs a laser beam on the surface of the metal substrate according to a preset scanning path. The scanning path is composed of multiple parallel micro-segments arranged side by side, with at least two parallel micro-segments, and in one specific embodiment, three.
[0032] A laser beam acts on a metal substrate along a scanning path, causing localized vaporization and melting of the metal surface material, and creating an array of micro-grid trenches in a designated area. After processing, a cleaning device removes the metal recasting residue around the micro-grid trenches to expose the openings and internal spaces of the micro-grid trenches, allowing them to accommodate subsequent polymer melt.
[0033] S30 achieves physical bonding between the metal substrate and the composite granules. The metal substrate with micro-grid grooves is positioned within the mold cavity of a thermoforming equipment. A specified mass of composite granules is laid in the processing area of the metal substrate. After the mold closes, the heating system raises the cavity temperature to the set processing temperature, and the hydraulic system applies molding pressure to the closed mold. The molten polypropylene matrix flows under pressure, wetting the surface of the metal substrate and penetrating into the micro-grid grooves.
[0034] S40 controls the cooling and solidification process of the composite material. After completing the set hot pressing cycle, the mold is closed and cooled. The composite material filled in the micro-grid grooves crystallizes and solidifies during cooling, forming mechanically embedded nodes that fit the groove structure. The demolding mechanism opens the mold and removes the composite component, which is then stored at room temperature to release the molding thermal stress within the material.
[0035] See attached document Figure 2 and attached Figure 7 Step S10 includes metal substrate pretreatment and composite particle preparation, specifically including the following sub-steps: S101, the cutting equipment obtains aluminum alloy sheets and processes them into metal substrates of a set size. The cutting equipment can be an electrical discharge machining (EDM) CNC wire cutting machine. The metal substrate can be processed into rectangular samples.
[0036] In one specific embodiment, the metal substrate has dimensions of 50mm × 10mm × 2mm. The thickness of the subsequently formed composite material layer is adapted to the thickness of the mold cavity and the metal gasket. The metal substrate and the composite material layer together form a composite component for tensile testing. If the actual test sample uses other thicknesses or overlap sizes, the dimensions of the metal substrate, composite material layer, and metal gasket can be adjusted according to the mold cavity and testing standards.
[0037] The processed metal substrate is transferred to a cleaning equipment for surface cleaning. The cleaning equipment is an ultrasonic cleaner containing an acetone solution. The metal substrate is immersed in the acetone solution and subjected to ultrasonic cleaning to remove processing residue, oil, and particulate impurities from the surface. The cleaned metal substrate is then placed in a drying equipment.
[0038] The drying equipment can be configured as an oven with a working temperature of 70°C. The metal substrate is kept in the oven for 30 minutes to complete the surface dehumidification treatment. The working fluid configuration of the EDM CNC wire cutting machine, the cleaning frequency and cleaning time of the ultrasonic cleaner can be set by those skilled in the art according to the size of the metal substrate, the degree of surface contamination and the equipment specifications. The equipment control and debugging are well known in the art and will not be described in detail here.
[0039] S102, the extrusion granulation equipment mixes polypropylene matrix and glass fiber to prepare composite granules. The polypropylene matrix and glass fiber are measured by weight percentage. In this embodiment, the mass fraction of glass fiber is 10% to 30%. In a specific embodiment, the mass fraction of glass fiber is selected as 10%, 20%, and 30% respectively to compare the effects of different glass fiber contents on the mechanical properties, rheological properties, and metal-plastic bond strength of the composite material.
[0040] The polypropylene matrix and glass fibers can be pre-dried before entering the extrusion granulation equipment. The pre-drying temperature and time can be determined based on the raw material moisture content, raw material packaging condition, and subsequent extrusion conditions. Pre-drying reduces the formation of bubbles from moisture and volatiles during high-temperature processing, thereby reducing porosity defects in the composite granules and subsequent metal-plastic interface. The dried material is then placed in a mixing device for pre-mixing, dispersing the glass fibers within the polypropylene matrix. The mixing speed and mixing time can be set by those skilled in the art based on the material dosage, glass fiber length, and mixing uniformity requirements; specific control methods are well-known in the field and will not be elaborated upon here.
[0041] S103, the premixed material is fed into a twin-screw extruder for melt blending and extrusion molding. The barrel of the twin-screw extruder is divided into multiple temperature-controlled sections along the material conveying direction. The temperature of each temperature-controlled section is set according to the melt processing temperature of the polypropylene matrix, so that the material is gradually plasticized and forms a continuous composite melt during the conveying process.
[0042] Each temperature control zone typically employs a configuration that gradually increases or maintains a stable temperature from the feed end to the die head to meet the requirements of polypropylene melting, glass fiber dispersion, and melt extrusion. Specific temperature zone values can be determined based on the polypropylene grade, glass fiber content, screw assembly, and extruder specifications.
[0043] The material is extruded by a twin-screw extruder to form a strip-shaped composite material. After cooling and curing, the strip-shaped composite material enters a pelletizer, which cuts the cured strips into composite pellets with a length of 3mm to 5mm. The cut composite pellets are then placed in an oven at 70℃ and dried for 3 hours.
[0044] After drying, the composite granules are cooled to room temperature and then sealed for storage to reduce moisture absorption and surface contamination. The structure of the cooling tank, the traction speed, and the pelletizer rotation speed can be set by those skilled in the art based on the strip diameter and the target granule length; the specific mechanical control is well-known in the field and will not be elaborated upon here.
[0045] S104. During twin-screw extrusion, the shearing action of the screws can cause glass fibers to break. To ensure that the glass fibers can play a reinforcing role in the composite material, the speed of the twin-screw extruder and the screw combination should avoid excessive breakage of the glass fibers. The ability of glass fibers to bear external loads in a polypropylene matrix is related to the fiber length.
[0046] When an external load is applied to the composite material, the polypropylene matrix deforms, and the stress is transferred to the glass fiber through the interfacial shear between the fiber and the matrix. If the glass fiber is too short, the central part of the fiber cannot reach its tensile breaking strength, and the fiber is easily pulled out of the matrix; if the glass fiber length reaches or exceeds the critical length, the fiber can bear the load more fully.
[0047] The critical length of glass fiber is estimated based on the shear hysteresis theory, and its calculation formula is as follows: ; In the formula, The critical length required for glass fiber to perform its effective load-bearing function, measured in millimeters; The tensile breaking strength of glass fiber is expressed in MPa. The cross-sectional diameter of the glass fiber is in millimeters. This represents the interfacial shear strength between the glass fiber and the polypropylene matrix, measured in megapascals (MPa). The tensile breaking strength of the glass fiber is also shown. and cross-sectional diameter Interfacial shear strength can be obtained from the specifications provided by the material supplier. It can be obtained through single fiber pull-out tests or interfacial shear strength tests commonly used in this field.
[0048] The above critical length calculation can serve as a basis for extrusion process control and glass fiber length verification. If it is necessary to confirm whether the glass fibers in the composite granules meet the load-bearing requirements, the length distribution of the glass fibers after extrusion can be statistically observed under a microscope and compared with the calculated critical length.
[0049] See attached document Figure 3and attached Figure 6 Step S20 alters the surface geometry of the metal substrate through laser processing, establishing the mechanical anchoring foundation required for the physical bonding of heterogeneous materials. The microtexturing and post-processing procedures performed in this step include the following sub-steps: S201, Set the laser processing path. Generate a grid-like scanning pattern in the control software. Due to the high thermal conductivity of aluminum alloy, conventional single-line high-energy scanning can easily cause localized molten metal to form recast material at the groove edge, thus affecting the groove opening morphology. To expand the processing width of a single grid line and control localized heat input, the single grid line in the scanning pattern is divided into multiple parallel micro-segments. In one specific embodiment, a single grid line consists of 3 parallel micro-segments, with a physical spacing of 10 μm between adjacent micro-segments.
[0050] In the overall scanning pattern, the center-to-center spacing between adjacent grid lines is set to 0.07 mm to 0.7 mm. Increasing the grid spacing reduces the microtexture density of the metal surface, thus decreasing the effective contact area between the metal and the composite material during subsequent composite molding. Conversely, if the grid spacing is too small, the heat-affected zones generated during the processing of adjacent grid lines tend to overlap, resulting in irregular surface undulations and affecting the groove morphology. Considering factors such as microtexture density, contact area, and heat-affected zone, a grid spacing of 0.1 mm is preferred.
[0051] S202, Configure the output parameters of the laser emitting device. The laser emitting device uses a laser with a wavelength of 1064nm. The scanning speed is configured between 800mm / s and 1200mm / s, preferably 1000mm / s. The laser power is configured between 20W and 30W, preferably 25W. The pulse frequency is configured between 20kHz and 50kHz, preferably 35kHz.
[0052] By combining laser power, scanning speed, and pulse frequency, the energy input per unit length and the degree of pulse overlap can be controlled to form controllable micro-grid grooves on the surface of the metal substrate, reducing the accumulation of recast material caused by excessive local heat input. The galvanometer deflection control, focal length adjustment, and stage positioning of the laser marking machine can be set by those skilled in the art according to the equipment model and operation manual; their operational configuration is well-known in the field and will not be elaborated upon here.
[0053] S203, Perform multiple laser scanning passes. The laser emitting device sequentially scans multiple micro-segments that make up a single grid line according to a set path. After a single micro-segment is scanned twice along the same path, the entire grid pattern is processed once, which is defined as one pass. In a specific embodiment, the laser emitting device performs a total of 10 scans on the complete grid pattern.
[0054] By creating micro-grid grooves of a certain depth and width through multiple scans, the composite melt can penetrate into the grooves during subsequent hot pressing. Compared to a single high-energy, slow scan, the multi-scan method distributes the groove machining depth across multiple scans, with each scan corresponding to a lower local heat input. This reduces the accumulation of recast material at the groove edges and the obstruction of the groove opening by metal spatter.
[0055] The aspect ratio of the micro-grid grooves increases with the number of scan passes. Too few scan passes result in insufficient groove depth and limited mechanical interlocking; too many scan passes increase the aspect ratio, making it difficult for the high-viscosity polymer melt to fully reach the bottom of the groove during hot pressing, easily leading to unfilled areas. In one specific embodiment, after 10 scan passes, the aspect ratio of the micro-grid grooves is 0.5. This morphology provides space for the composite melt to enter the grooves and reduces incomplete filling caused by excessive groove depth.
[0056] S204. After laser scanning, recast material formed by the cooling of molten metal adheres to the surface of the metal substrate and the edges of the micro-grid trenches. The metal substrate is transferred to a polishing machine for surface grinding to remove protruding recast metal nodules. The ground metal substrate is then placed in an ultrasonic cleaner to remove tiny particles remaining inside or at the edges of the micro-grid trenches in the cleaning solution. The cleaned metal substrate is then dried with a hot air gun to expose the openings and internal spaces of the micro-grid trenches, providing interface conditions for subsequent composite melt wetting and filling.
[0057] See attached document Figure 4 and attached Figure 8 Step S30 achieves physical bonding between the metal substrate and the composite granules through hot pressing. The hot pressing assembly, rheological filling, and temperature control process performed in this step includes the following sub-steps: S301, the metal substrate with micro-grid grooves is moved into the mold cavity of the hot press forming machine. To control the overlap area between the metal and the composite material and to ensure the alignment of the tensile axis in subsequent mechanical testing, metal gaskets are placed in the non-connected areas at both ends of the metal substrate. The metal gaskets act as limiting members, and their dimensions are adapted to the mold cavity and the test sample dimensions. In one specific embodiment, the bonding area between the metal and the composite material is configured as 10mm × 10mm. The thickness of the metal gaskets can be consistent with the thickness of the metal substrate to ensure a stable pressure distribution applied to the overlap area when the upper and lower molds are closed.
[0058] After placing the metal gasket, the prepared composite granules are spread over the micro-grid groove area of the metal substrate, completing the material arrangement before mold closing. The amount of composite granules is determined based on the mold cavity volume, the target composite material layer thickness, and the overlap area size between the metal and composite material, so that the composite material layer formed after hot pressing can cover the micro-grid groove area of the metal substrate.
[0059] S302, Start the heating system of the hot press molding equipment to heat the mold. The composite granules change from a solid state to a molten state after being heated. When the composite melt flows in the cavity, it usually exhibits shear-thinning behavior as a non-Newtonian pseudoplastic fluid, and its flow state can be characterized by rheological relationships.
[0060] As temperature increases, the mobility of polypropylene molecular chain segments increases, and the viscosity of the composite melt decreases. Under shear stress, polypropylene molecular chains and some glass fibers orient along the flow direction, reducing the internal flow resistance of the melt. When evaluating the effects of different glass fiber contents or different molding temperatures on melt flowability, the steady-state flow relationship can be described by a power-law equation: ; In the formula, The shear stress of the composite melt is expressed in Pascals (Pa). The fluid consistency index characterizes the viscosity of a composite melt, measured in Pascals per second (Pa·s). Power; Shear rate, measured in seconds; These are non-Newtonian exponents. For pseudoplastic fluids, Less than 1. Fluid consistency index Non-Newtonian exponents The results can be obtained by testing with a rotational rheometer or a capillary rheometer at a set temperature. This rheological relationship can be used to evaluate the ability of composite melts with different glass fiber contents and at different molding temperatures to enter micro-grid channels.
[0061] S303: The hydraulic system applies forming pressure to the closed mold, causing the heated composite melt to spread onto the surface of the metal substrate under pressure and enter the interior of the micro-grid grooves through the openings. As the melt enters the grooves, air inside the grooves is expelled towards the groove openings, and the composite melt gradually adheres to the sidewalls and bottom area of the grooves.
[0062] The molding pressure can be set according to the mold cavity size, composite granule dosage, glass fiber content, and melt flow state. After applying pressure, it should be maintained for a certain time to allow the composite melt to fill the micro-grid grooves and reduce the possibility of excessive melt overflow from the cavity edges due to excessive pressure. The matching of molding pressure and holding time is based on the control criteria of ensuring the composite melt enters the micro-grid grooves, the overlapping area is completely formed, and excessive overflow occurs at the cavity edges.
[0063] If visible gaps or unfilled areas exist in the bonding area after demolding, the melt filling state can be improved by increasing the molding temperature, extending the holding time, or adjusting the molding pressure. The hot press molding cycle includes mold heating, composite granule plasticization, molding pressure application, and pressure holding. For the drive control of the hydraulic cylinder of the hot press molding machine and the sealing structure of the mold cavity, those skilled in the art can adjust them according to the equipment operation manual; the equipment control is well-known technology in the field and will not be elaborated further here.
[0064] In S304, the molding temperature and glass fiber content during hot pressing jointly affect the filling quality of the composite melt. The molding temperature is set between 190℃ and 230℃. At lower temperatures, the composite melt viscosity is higher, resulting in greater flow resistance and increased difficulty for the melt to enter the bottom of the micro-grid grooves. At higher temperatures, the composite melt viscosity decreases, which is beneficial for wetting the surface of the metal substrate and entering the grooves. However, if the viscosity is too low, the composite melt is prone to overflowing towards the cavity edge under pressure, reducing the effective pressure acting on the bonding area.
[0065] The glass fiber content also affects melt flow and load transfer. Lower glass fiber content results in better melt flow, but the composite material itself has limited load-bearing capacity. Higher glass fiber content increases the stiffness and strength of the composite material, but reduces melt flow and increases the difficulty of filling the grooves. In one specific embodiment, glass fiber reinforced polypropylene with a glass fiber mass fraction of 20% is hot-pressed onto an aluminum alloy substrate. The molding temperature can be selected from 190℃, 210℃, and 230℃ for comparison.
[0066] By matching the molding temperature with the glass fiber content, the composite melt is made capable of flowing into the micro-grid grooves and possesses the material strength to transmit external loads after cooling and solidification. The molding temperature is used to adjust the apparent viscosity of the composite melt, while the glass fiber content is used to adjust the flowability of the composite material and its load-bearing capacity after solidification. Both factors jointly affect the filling state of the micro-grid grooves and the interfacial bonding strength of the composite component.
[0067] See attached document Figure 5 Step S40 controls the cooling and curing process of the composite component after hot pressing, enabling the composite material entering the micro-grid grooves to form a stable mechanically embedded structure. The cooling, demolding, and residual stress release process performed in this step includes the following sub-steps: S401, after completing the set hot pressing cycle, the mold is cooled. The mold can remain closed during cooling, ensuring that the metal substrate and composite material remain in contact during the initial cooling phase. Cooling can be achieved through natural cooling or circulating media cooling. When using circulating media cooling, the cooling medium enters the cooling channels inside the mold, causing the temperature of the upper and lower molds to decrease. The cooling water circuit connection method, circulating pump start / stop control, and temperature sensing element arrangement of the hot pressing machine can be set by those skilled in the art based on the mold structure and equipment operation manual. The equipment connection and control are well-known technologies in the field and will not be elaborated upon here.
[0068] In S402, during the cooling process, the composite material gradually transforms from a molten state to a solidified state. The polypropylene matrix crystallizes and shrinks in volume during cooling, while the glass fibers restrict some of the matrix's shrinkage and deformation. If the composite material experiences relative displacement with the metal substrate before full solidification, the composite material entering the micro-grid grooves may become loose or form interfacial voids. Keeping the mold closed during the cooling stage helps to confine the composite material, limiting the thickness-direction deformation of the composite melt within the micro-grid grooves during crystallization and solidification, and allowing the composite material within the grooves to solidify and form according to the groove contour.
[0069] After the composite melt enters the micro-grid trenches, it forms solidified regions that match the trench contours during the cooling and solidification process. These solidified regions are constrained by the trench sidewalls, thus preventing the composite material from sliding along the metal substrate surface under tensile loads. The solidified composite material filling the micro-grid trenches occupies the internal space of the trenches, and the trench sidewalls provide geometric constraints on the solidified material. These connections constitute mechanically anchored nodes. These mechanically anchored nodes resist debonding or slippage of the composite component along the interface direction under tensile loads.
[0070] S403, after the mold temperature drops to a level where the composite material has cured and is suitable for demolding, the hydraulic system releases the clamping force or remaining molding pressure, and the demolding mechanism opens the mold and removes the composite component. The demolding temperature can be determined based on the curing state of the composite material, the mold structure, and operational safety requirements. After removing the composite component, remove the metal gaskets located in the non-connection areas and check whether the overlap area between the metal substrate and the composite material is intact. The mold opening stroke, ejection mechanism position, and mold surface demolding treatment method of the demolding mechanism can be set by those skilled in the art based on the size of the composite component and the mold structure. The specific mechanical structure is well-known in the art and will not be described further here.
[0071] S404: After demolding, the composite component is placed in a room-temperature dry environment for static storage to release residual thermal stress generated during the molding process. The room-temperature dry environment can be an indoor ambient temperature environment, in which the composite component is placed horizontally, and the overlapping areas are not subjected to external clamping forces or bending loads. In one specific embodiment, the composite component is placed at room temperature for 48 hours before undergoing mechanical property testing.
[0072] Due to the different coefficients of thermal expansion between aluminum alloy and glass fiber reinforced polypropylene, the amount of shrinkage they produce during cooling differs, and there is a possibility of residual thermal stress at the interface. By allowing the composite component to stand at room temperature, the shrinkage thermal stress inside is released, and the subsequent tensile test results can more stably reflect the mechanical interlocking effect formed between the micro-grid grooves and the composite material.
[0073] In a specific application example: Example 1: A method for improving the bonding strength between fiber-reinforced polypropylene composites and aluminum alloys includes the following steps: 1. Cut aluminum alloy sheets into samples and ultrasonically clean the surface of the metal samples with acetone solution; 2. Place the metal sample on the stage of the laser marking machine, import the drawn pattern for laser processing. The laser parameters are: scanning speed 1000mm / s, power 25W, frequency 35kHz. After scanning each line twice along the same path, the entire grid pattern is processed once, which is defined as one pass. Scan the aluminum alloy sample 10, 15, and 20 times respectively, with a grid spacing of 0.3mm. After scanning, use a polishing machine and an ultrasonic cleaner to remove the surface recast layer. 3. Use a super depth-of-field microscope to observe the depth and width of the microtexture and calculate the aspect ratio; 4. Hot-press composite with GFRPP component containing 20% glass fiber, cool and demold, place at room temperature for 48 hours to release internal stress, and then test with a tensile testing machine.
[0074] In this embodiment, the number of scans of the microtexture on the aluminum alloy surface was changed. As the number of scans increased, the texture depth and the heat-affected zone also changed, leading to changes in the bonding strength. The results are shown in Table 1. Table 1:
[0075] As shown in Table 1, although increasing the number of scan passes increases the depth of the microtexture, the range of width variation is relatively small, meaning the depth-to-width ratio of the microtexture increases (0.5 for 10 scan passes, 1.97 for 20 scan passes). Furthermore, with a fixed laser head height and an increasing number of scan passes, the increase in depth decreases, thus reducing the impact on bonding strength. Based on the tensile strength at 20 scan passes, the tensile strength at 10 scan passes increases by 6.7%.
[0076] Example 2: A method for improving the bonding strength between fiber-reinforced polypropylene composites and aluminum alloys includes the following steps: 1. Cut aluminum alloy sheets into samples and ultrasonically clean the surface of the metal samples with acetone solution; 2. Place the metal sample on the stage of the laser marking machine, import the drawn pattern for laser processing. The laser parameters are: scanning speed 1000mm / s, power 25W, frequency 35kHz. After scanning each line twice along the same path, the entire grid pattern is processed once, which is defined as one pass. Scan the aluminum alloy sample 10 times. The grid spacing is 0.07mm, 0.1mm, 0.3mm, 0.5mm, and 0.7mm. After scanning, use a polishing machine and an ultrasonic cleaner to remove the surface recast layer. 3. Hot-press composite with GFRPP component containing 20% glass fiber, cool and demold, place at room temperature for 48 hours to release internal stress, and then test with a tensile testing machine.
[0077] In this embodiment, the mesh spacing of the microtexture on the aluminum alloy surface was changed. As the mesh spacing changed, the texture density changed, the contact area with the polymer also changed, and this led to differences in the bonding strength. The results are shown in Table 2. Table 2:
[0078] As shown in Table 2, within the range of a spacing of not less than 0.1 mm, the smaller the mesh spacing, the greater the overall tensile strength of the composite joint. This is because, with a fixed processing area, the density of the microtexture decreases when the mesh spacing increases, thus reducing the contact area between GFRPP and the aluminum alloy surface. Furthermore, as the laser scanning spacing increases, the heat-affected zone decreases, and the depth and width of the microtexture are slightly reduced compared to meshes with smaller spacing.
[0079] When the mesh spacing was reduced to 0.07 mm, the bonding performance did not improve significantly. This is because as the spacing decreased further, the heat-affected zones of adjacent lines overlapped, causing mutual influence. Each mesh was affected multiple times, resulting in an irregular surface microtexture and rapid surface undulations. This also caused changes in surface stress in the aluminum alloy, leading to a slight decrease in bonding strength, although it was still better than the 0.5 mm and 0.7 mm meshes. In summary, this indicates that the prepared microtexture density should not be too low. Increasing the contact area of the aluminum-plastic dissimilar material connection surface can effectively improve the bonding strength of the composite joint. The bonding strength at a 0.1 mm spacing was 21.3% higher than that at 0.5 mm.
[0080] Example 3: A method for improving the bonding strength between fiber-reinforced polypropylene composites and aluminum alloys includes the following steps: 1. Cut aluminum alloy sheets into samples and ultrasonically clean the surface of the metal samples with acetone solution; 2. Place the metal sample on the stage of the laser marking machine, import the drawn pattern for laser processing. The laser parameters are: scanning speed 1000mm / s, power 25W, frequency 35kHz. After scanning a single line twice along the same path, the entire grid pattern is processed once, which is defined as one pass. Scan the aluminum alloy sample 10 times with a grid spacing of 0.3mm. After scanning, use a polishing machine and an ultrasonic cleaner to remove the surface recast layer. 3. In this embodiment, polypropylene is abbreviated as PP, and glass fiber reinforced polypropylene composite material is abbreviated as GFRPP. PP is used as a comparative example, and GFRPP with glass fiber content of 10%, 20%, and 30% are used as example groups. They are respectively hot-pressed with aluminum alloy samples, cooled and demolded, and placed at room temperature for 48 hours to release internal stress before being tested with a tensile testing machine.
[0081] In this embodiment, the glass fiber ratio of the polymer used for composite molding was varied. Different glass fiber contents resulted in varying mechanical and rheological properties of the polymer, thus exploring its impact on the bonding strength of the composite component. The results are shown in Table 3. Table 3:
[0082] As shown in Table 3, the bonding strength of the joint first increases and then decreases with the increase of glass fiber content. Pure PP itself has a large elongation at break; however, in the interfacial tensile test of aluminum alloy and PP composite components, the failure occurred in the region of PP near the interface, and the fracture mode was brittle fracture. This is because there is stress concentration in the mesh microtexture, in which PP is strongly constrained, and its plastic deformation ability is severely suppressed, resulting in a behavior transition from toughness to brittleness, which leads to debonding of the interface under low stress.
[0083] When the glass fiber content is 30%, the high glass fiber content results in insufficient compatibility with the PP matrix and deteriorated melt flowability, leading to a decrease in the bonding strength with the aluminum alloy compared to the component with 20% glass fiber content. The bonding strength reaches its maximum at a glass fiber content of 20%, which can be attributed to the combined influence of glass fiber on matrix properties, melt flowability, and interface structure. At this level, the matrix possesses suitable stiffness and strength, enabling the transfer of load to the mechanically embedded nodes. Simultaneously, it facilitates the filling of micro-grid grooves during hot pressing, resulting in a superior stress synergy effect within the test range. The bonding strength at this level is 71.4% higher than that of PP.
[0084] Example 4: A method for improving the bonding strength between fiber-reinforced polypropylene composites and aluminum alloys includes the following steps: 1. Cut aluminum alloy sheets into samples and ultrasonically clean the surface of the metal samples with acetone solution; 2. Place the metal sample on the stage of the laser marking machine, import the drawn pattern for laser processing. The laser parameters are: scanning speed 1000mm / s, power 25W, frequency 35kHz. After scanning a single line twice along the same path, the entire grid pattern is processed once, which is defined as one pass. Scan the aluminum alloy sample 10 times with a grid spacing of 0.3mm. After scanning, use a polishing machine and an ultrasonic cleaner to remove the surface recast layer. 3. Hot-press composite with GFRPP component containing 20% glass fiber, molding temperatures are 190℃, 210℃, and 230℃ respectively. After cooling and demolding, place at room temperature for 48 hours to release internal stress, and then test with a tensile testing machine. 4. Subsequently, three sets of tensile tests were conducted on GFRPP and aluminum alloy with different glass fiber contents at 230℃, and the results were compared.
[0085] In this embodiment, the hot pressing temperature of aluminum alloy and GFRPP material was changed, and the results are shown in Table 4: Table 4:
[0086] From the data in Table 4, "-" indicates that the corresponding combinations of glass fiber content and molding temperature were not tested. A cross-sectional observation shows that when the glass fiber content is 20%, the bond strength measured at different temperatures increases with increasing temperature. This is because higher temperatures reduce melt viscosity, improve its flow properties, and make it easier to enter the micro-grid grooves, thereby improving the groove filling depth and mechanical embedding effect. The increase in temperature leads to a 25.6% increase in bond strength.
[0087] The same principle applies when the glass fiber content is 30%. However, when the glass fiber content is 10%, the increase in temperature does not improve the bonding strength. This is because the glass fiber content is low. PP is a typical semi-crystalline thermoplastic material, and its melt viscosity is very sensitive to temperature. At 230℃, the viscosity is too low, resulting in very good melt flowability. At this time, under hot pressing pressure, the melt is more likely to wet the surface of the metal substrate and enter the micro-grid grooves, while also spreading outwards. Therefore, in the closed cavity, due to the extrusion of the melt, the system pressure will decrease, which shortens the effective filling time and results in insufficient pressure holding time on the interface. The melt is difficult to fully fill the micro-grid grooves, and air bubbles and unfilled pores are easily left at the bottom of the microtexture. At lower temperatures, the melt can more evenly and continuously transmit the pressure applied by the hot press to the interface and deep within the microtexture, while also helping to limit the migration of glass fibers and ensure their stable distribution within the composite material, thus uniformly bearing the load. Therefore, it is important to select an appropriate temperature to achieve a balance between material flowability and pressure maintenance, rather than solely considering flowability.
[0088] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for improving the bonding strength between fiber-reinforced polypropylene composites and aluminum alloys, characterized in that, include: Aluminum alloy sheet is processed into metal substrate, and polypropylene matrix is melt-blended with glass fiber and granulated to obtain composite granules; A laser beam is output along a grid-like scanning path on the surface of the metal substrate to process micro-grid trenches. The grid-like scanning path includes multiple grid lines. Each grid line is composed of three parallel micro-segments arranged side by side. The physical spacing between adjacent micro-segments is 10 μm, and the center-to-center spacing between adjacent grid lines is set to 0.07 mm to 0.7 mm. When a laser beam is output on the surface of the metal substrate, a single micro-segment is scanned twice along the same path before completing one processing of the complete mesh pattern, which is defined as one pass; a total of 10 passes are performed on the complete mesh pattern so that the aspect ratio of the processed micro-mesh groove is 0.5; the laser parameters are scanning speed 1000mm / s, power 25W, and frequency 35kHz. A mold with a mold cavity is provided, the metal substrate is positioned in the mold cavity, the composite granules are laid on the area of the metal substrate with the micro-grid grooves, the mold is closed, the mold is heated to transform the composite granules into a composite melt, and molding pressure is applied and held to allow the composite melt to enter the interior of the micro-grid grooves. The mold in the closed state is cooled down to allow the composite melt located inside the micro-grid grooves to crystallize and solidify, resulting in a composite component. The mold is then opened to remove the composite component. After the aluminum alloy sheet is processed into a metal substrate, the metal substrate is subjected to surface cleaning and dehumidification treatment. After the micro-grid trenches are fabricated and before the composite granules are laid, the surface of the metal substrate is cleaned, including: The metal substrate with the micro-grid grooves is subjected to surface polishing to remove the protruding recast metal nodules on the surface of the metal substrate. The polished metal substrate is placed in an ultrasonic cleaner for cleaning to remove tiny particles remaining inside and at the edges of the micro-grid grooves. The cleaned metal substrate is dried with hot air to expose the openings and internal spaces of the micro-grid trenches.
2. The method for improving the bonding strength between fiber-reinforced polypropylene composite materials and aluminum alloys according to claim 1, characterized in that, When the metal substrate is positioned in the mold cavity, metal gaskets are placed in the non-connection areas at both ends of the metal substrate, and the metal gaskets serve as limiting members. The thickness of the metal pad is consistent with the thickness of the metal substrate, so as to stabilize the pressure distribution applied to the region of the metal substrate with the micro-grid grooves when the mold is closed.
3. The method for improving the bonding strength between fiber-reinforced polypropylene composite materials and aluminum alloys according to claim 1, characterized in that, The target temperature for heating the mold is set to 190°C to 230°C.
4. The method for improving the bonding strength between fiber-reinforced polypropylene composite materials and aluminum alloys according to claim 3, characterized in that, The glass fiber in the composite granules is configured to have a mass fraction of 20%, and the target temperature for heating the mold is 210°C to 230°C.
5. The method for improving the bonding strength between fiber-reinforced polypropylene composite materials and aluminum alloys according to claim 1, characterized in that, The process of melt blending and granulating the polypropylene matrix with the glass fiber includes: feeding the polypropylene matrix and the glass fiber into a twin-screw extruder for melt blending and extrusion molding; The rotational speed and screw combination of the twin-screw extruder are checked according to the critical length of the glass fiber to avoid excessive breakage of the glass fiber; The critical length is estimated based on the shear hysteresis theory and determined by the following relationship: the product of the tensile breaking strength of the glass fiber and the cross-sectional diameter of the glass fiber, divided by twice the interfacial shear strength between the glass fiber and the polypropylene matrix.
6. The method for improving the bonding strength between fiber-reinforced polypropylene composite materials and aluminum alloys according to claim 1, characterized in that, When cooling the mold in a closed state, the mold is kept closed during the cooling stage to limit the thickness deformation of the composite melt located inside the micro-grid grooves during the crystallization and solidification process; The micro-grid grooves form a geometric constraint on the crystallized and solidified composite melt, constituting a mechanically embedded node. The mechanically embedded node is used to resist the debonding or slippage of the composite component along the interface direction under tensile load.
7. The method for improving the bonding strength between fiber-reinforced polypropylene composite materials and aluminum alloys according to claim 1, characterized in that, After opening the mold and removing the composite component, the composite component is left to stand for storage, which includes: The removed composite component was placed horizontally in a dry environment at room temperature and left to stand for 48 hours. During static storage, the area in the composite component where the metal substrate is joined to the crystallized and solidified composite melt is not subjected to external clamping force and bending load, so as to release the shrinkage thermal stress remaining during cooling due to the difference in the coefficient of thermal expansion between the metal substrate and the crystallized and solidified composite melt.
Citation Information
Patent Citations
Connecting method of metal and thermoplastic fiber reinforced composite material
CN121777433A